Characterizing summer and winter carbonyl compounds in Beijing atmosphere - X. Qian; H.Q. Shen; Chen, Z. M. (Atmospheric Environment, 2019)
Carbonyl compounds (carbonyls) play important roles in atmospheric photochemistry, serving as reservoirs of radicals (OH, HO2, and RO2) and precursors of secondary organic aerosols (SOA). Field measurements of gaseous and particulate carbonyls were taken over urban Beijing during summer and winter, and field-measured gas-particle partitioning coefficients (Kp ) were determined. Compared with theoretical values, field-measured Kp values were 4–6 orders of magnitude higher for the six detected carbonyls, which underlined the importance of heterogeneous reactions. In winter, the Kp values of carbonyl compounds were one order of magnitude higher than those in summer owing to the effect of temperature. This study applied the positive matrix factorization (PMF) model to the source apportionment of carbonyl compounds. Five factors were identified for both summer and winter, whereas the biogenic factor was only identified in summer and coal burning was only found in winter. In summer, secondary formation was the largest contributor (39%) to the measured total carbonyl compounds levels. In contrast, vehicular exhaust was the largest source of the measured total carbonyl compounds in winter (37%), although secondary formation still had an important contribution of 31%. The contribution of coal burning to ambient carbonyls was reduced by half compared with prior results. As the most abundant carbonyl compound in the atmosphere, formaldehyde in summer mainly came from secondary production (42%) and primary anthropogenic emissions (48%), while biogenic sources had a minor contribution (10%). However, 78% of formaldehyde was attributed to primary anthropogenic emissions in winter, which indicated that these winter emissions were more important sources of carbonyl compounds. Glyoxal was always dominated by secondary formation, with contributions of 56% in summer and 52% in winter.